MODERN MECHANISMS FOR ENHANCING THE INVESTMENT ATTRACTIVENESS OF COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2026)
This article comprehensively examines modern mechanisms for enhancing the investment attractiveness of commercial banks, factors stimulating investment activity within the banking system, and directions for ensuring financial stability. The study analyzes the impact of capital adequacy, asset quality, profitability, liquidity indicators, digital banking services, and corporate governance systems on the investment attractiveness of commercial banks. Furthermore, based on international banking practices and the experience of developed countries, scientific and practical recommendations aimed at strengthening the investment potential of commercial banks in Uzbekistan are proposed. The research substantiates mechanisms designed to reduce investment risks, strengthen investor confidence, and improve the competitiveness of banks in international financial markets.